Transaksi Darah untuk Transfusi Darah Menurut Perspektif Hukum Islam: Analisis Akad Tabarru’ dan Ijarah - Nur Azizah; M. Mutamakin; Ansari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study examines the legal status of blood transactions used for blood transfusions from the perspective of Islamic law, with emphasis on the concepts of akad tabarru’ and akad ijarah. The research analyzes the mechanisms of blood collection, management, and distribution at the Blood Donation Unit of PMI Banyuwangi, deepening understanding of the legal status of blood transactions. Employing a qualitative method with a narrative approach involving interviews and literature review, the findings indicate that blood transfusion falls under akad tabarru’, a contract without compensation aimed at mutual help based on the principle of cooperation (ta’awun). The novelty of this research lies in its specific analysis of the blood processing fee (BPPD), which is categorized as akad ijarah, where the fee is a payment for blood management services, not the result of selling the blood itself. This study provides a theoretical contribution to contemporary fiqh by clearly distinguishing between the human aspect (blood donation) and operational costs. The research emphasizes that blood transactions in a medical context must be based on humanitarian values, solidarity, and adhere to the principles of Sharia in both akad tabarru’ and akad ijarah.